2012
DOI: 10.1681/asn.2012010053
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies Targeting Galactose-Deficient IgA1 Associate with Progression of IgA Nephropathy

Abstract: Mesangial and circulating IgA1 with aberrantly glycosylated hinge region O-glycans characterize IgA nephropathy (IgAN). Unlike healthy individuals, some IgA1 is galactose deficient in patients with IgAN, leaving terminal N-acetylgalactosamine residues in the hinge region exposed. Circulating autoantibodies that recognize such galactose-deficient IgA1 as an autoantigen, or the levels of the autoantigen itself, may allow prediction of disease progression. Here, we analyzed serum samples obtained at diagnosis for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
155
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(168 citation statements)
references
References 34 publications
11
155
0
Order By: Relevance
“…Several studies have also reported minimal or even no differences between galactosylation of IgA1 from IgAN patients and IgA1 from control donors, showing in their data similar reactivity with lectins (HAA, HPA or VVA) specific to galactose-deficient O-glycans (48,60,61). Yet, the conclusions of many of these reports identify galactose-deficient IgA1 as a hallmark of IgAN and as a marker to discriminate between IgAN patients and healthy individuals.…”
Section: Discussionmentioning
confidence: 90%
“…Several studies have also reported minimal or even no differences between galactosylation of IgA1 from IgAN patients and IgA1 from control donors, showing in their data similar reactivity with lectins (HAA, HPA or VVA) specific to galactose-deficient O-glycans (48,60,61). Yet, the conclusions of many of these reports identify galactose-deficient IgA1 as a hallmark of IgAN and as a marker to discriminate between IgAN patients and healthy individuals.…”
Section: Discussionmentioning
confidence: 90%
“…Polymeric IgA1 molecules with a reduced content of galactose-carrying GalNac residues (Gd-IgA1) are found in Henoch-Schönlein purpura nephritis and IgA-nephritis patients [35]. The finding of IgA antibodies directed against Gd-IgA1 could explain the lack of IgG deposition, but in a different study although the serum levels of IgA and IgG antibodies against Gd-IgA1 correlated with the clinical progression of IgAN, not all patients had increased levels compared to controls and none showed renal IgG deposition [36]. Therefore, it remains to be proven whether serum antibodies against GdIgA1 are a specific requirement for the formation of the renal IgA1-containing immune complexes found in IgAN.…”
Section: Etiology and Pathophysiologymentioning
confidence: 93%
“…The following processes are involved in the pathogenesis (7) of IgAN: aberrant glycosylation of IgA1 (8), synthesis of antibodies directed against galactosedeficient IgA1, binding of the galactose-deficient IgA1 by antibodies to form immune complexes, and deposition of these complexes in the glomerular mesangium, inducing activation of mesangial cells and glomerular damage (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%